Alkylated EDTA potentiates antibacterial photodynamic activity of protoporphyrin - Ying Piao; Sebastian Himbert; Zifan Li; Jun Liu; Zhihao Zhao; Huahai Yu; Shuangshuang Liu; Shiqun Shao; Michael Fefer; Maikel C. Rheinstädter; Youqing Shen (Journal of Nanobiotechnology, 2024)
Abstract Antibiotic resistance has garnered significant attention due to the scarcity of new antibiotics in development. Protoporphyrin IX (PpIX)-mediated photodynamic therapy shows promise as a novel antibacterial strategy, serving as an alternative to antibiotics. However, the poor solubility of PpIX and its tendency to aggregate greatly hinder its photodynamic efficacy. In this study, we demonstrate that alkylated EDTA derivatives (aEDTA), particularly C14-EDTA, can enhance the solubility of PpIX by facilitating its dispersion in aqueous solutions. The combination of C14-EDTA and PpIX exhibits potent antibacterial activity against Staphylococcus aureus (S. aureus) when exposed to LED light irradiation. Furthermore, this combination effectively eradicates S. aureus biofilms, which are known to be strongly resistant to antibiotics, and demonstrates high therapeutic efficacy in an animal model of infected ulcers. Mechanistic studies reveal that C14-EDTA can disrupt PpIX crystallization, increase bacterial membrane permeability and sequester divalent cations, thereby improving the accumulation of PpIX in bacteria. This, in turn, enhances reactive oxygen species (ROS) production and the antibacterial photodynamic activity. Overall, this effective strategy holds great promise in combating antibiotic-resistant strains. Graphical Abstract